1998
DOI: 10.1023/a:1005954621558
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pectin methylesterase (PME) is responsible for the demethylation of pectin prior to pectin's degradation by the combined activities of polygalacturonase and pectate lyase. We have differentially screened a maize pollen cDNA library to detect cDNA clones whose genes are specifically expressed in pollen. One group of clones resulting from this screen showed similarity (between 18% and 41% identity) with plant and fungal PMEs. The full-length clone from this group, ZmC5, identifies a small gene family (at least 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Note that in view of the high expression of AtPMEI1 and 2 in pollen, it is unclear whether the PME activity extracted from flowers and used as in vitro target enzyme in this study (see above) is the same PME isoform expressed in pollen. However, PME genes specifically expressed in pollen have been previously characterized for several plant species [8,9]. As during pollen formation and, in particular, during pollen tube growth the process of PME‐mediated pectin deesterification appears to be under tight control, both spatially and temporally, an interaction of PME with PMEI proteins may be part of this regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in view of the high expression of AtPMEI1 and 2 in pollen, it is unclear whether the PME activity extracted from flowers and used as in vitro target enzyme in this study (see above) is the same PME isoform expressed in pollen. However, PME genes specifically expressed in pollen have been previously characterized for several plant species [8,9]. As during pollen formation and, in particular, during pollen tube growth the process of PME‐mediated pectin deesterification appears to be under tight control, both spatially and temporally, an interaction of PME with PMEI proteins may be part of this regulation.…”
Section: Resultsmentioning
confidence: 99%
“…PME genes may be separated into two classes: type I genes contain two or three introns and the deduced proteins include a long pro‐region, whereas type II genes contain five or six introns and the pro‐region of the deduced proteins is missing in most cases [2]. Earlier studies revealed that expression of PME genes is strongly regulated in a tissue‐specific manner [6–9].…”
Section: Introductionmentioning
confidence: 99%
“…pectin methylesterase, ascorbate oxidase, β‐galactosidase, polygalacturonase) in cluster II‐a. These proteins have been previously reported to be specifically expressed during late pollen development and to play an active role during pollen germination and pollen tube growth [27–30].…”
Section: Resultsmentioning
confidence: 99%
“…The antisense expression of BoPMEI1 in Arabidopsis reduced the expression of its Arabidopsis ortholog and resulted in reduced pollen tube growth and poor seed set (Zhang et al 2010). Several species-specific PME genes, Bp19 from Brassica napus, PPE1 from Petunia inflata, ZmC5 from Maize and OsPME1 from Rice, specifically expressing in the later stages of pollen development have been identified (Mu et al 1994;Wakeley et al 1998;Kanneganti and Gupta 2009;Alabani et al 1991). However, these genes have not been functionally characterized.…”
Section: Pmes/pmeis In Pollen Tube Growthmentioning
confidence: 99%